Designing eco label to influence consumer perchase intention / Harlina Abdul Rasid - Abdul Rasid, Harlina (2014)
Environmental friendly products and services have got more attention during recent years. Every year consumers and companies are becoming increasingly aware and concerned about the effect on our environment. One form of environmental friendly products is eco label which have got more relevance for the consumers in the buying decisions and there are more product choose among them. In Malaysia, an eco label is still new. Government of Malaysia launched the eco label called MyHijau on December 2012. The MyHijau label is included product and services. MyHijau label will promotes a better understanding of environmentally safe purchase to consumers'. It will be a guide to consumers who are preferred to buy green product and use a green services. But is that Malaysia consumers' are ready for the eco label? Are they know that Malaysia have a eco label and did they recognize the eco label? The main purpose of the research is to study the about the eco label and did designing eco label can influence the consumers' purchase intention.